The Reviews on Sustainable and Responsible Investment (SRIs) Practices According to Maqasid Shariah and Maslahah Perspectives - Muhammad Zarunnaim Haji Wahab; Asmadi Mohamed Naim (ETIKONOMI, 2021)
The present study aims to explore SRIs practices based on Maqasid Shariah and Maslahah's points of view. A qualitative method via content analysis document was advocated to address the link between all concepts. The analysis revealed that SRIs, Maqasid Shariah and Maslahah share similar aims and goals to promote better environmental practices and social and governance issues. Thus, the paper concludes that the concept of SRIs does not contradict Maqasid Shariah and Maslahah in Islamic perspectives. However, a few criteria in the Environmental, Social and Governance (ESG) concept that govern the SRIs practices like promoting human rights, freedom of expression, and censorship need further clarification to align with Shariah principles. The paper can enlighten the reader, especially in terms of the capabilities of SRIs practices (which is from West philosophy) to suit Maqasid Shariah and Maslahah in Islamic perspectives.JEL Classification: G2, G4, I13, N2How to Cite:Wahab, M. Z. H., & Naim, A. M. (2021). The Reviews on Sustainable and Responsible Investment (SRIs) Practices According to Maqasid Shariah and Maslahah Perspectives. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.18053.